Preparation and characterization of Gliclazide incorporated Cellulosic Microspheres: studies on drug release, compatibility and micromeritics - Ayon, Navid Jubaer; Hasan, Ikramul; Islam, Md Shfiqul; Reza, Md Selim (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Polymeric microspheres of gliclazide were prepared to provide sustained release delivery of gliclazide to aid in continuous therapy with high margin of safety. Gliclazide was microencapsulated with different polymers namely HPMC K100LV, Ethocel (20 cps) and HPMC K100M by emulsion solvent evaporation technique using acetone as internal phase and liquid paraffin as external phase. Seventeen formulations were prepared using different drug loading and polymeric ratio of which nine formulations were prepared by a 32 full factorial design. Each formulation was evaluated for flow properties, particle size, surface morphology, drug entrapment efficiency, drug release and compatibility. Yield (%) for every batch of microspheres was measured. Flow properties of the microspheres were examined by determining bulk density, tapped density, Carrs compressibility index, Hausner ratio and angle of repose. Particle size distribution was examined by sieving and particle size analyzer. Surface morphology was determined by scanning electron microscopy (SEM). In-vitro drug release was studied in a paddle type dissolution apparatus (USP Type II Dissolution Apparatus) for a period of 8 hours at 37°C using phosphate buffer ( pH 7.4). FTIR and DSC studies established compatibility of the drug with the polymers. Microspheres prepared with Ethocel (20 cps) and HPMC K100M were free flowing than those prepared only with HPMC K100LV. Entrapment efficiencies were within 75.88-99.69%. Microspheres prepared with Ethocel (20 cps) and HPMC K100M showed more sustained release when compared to microspheres prepared with HPMC K100LV only. Increase in drug loading resulted in increased drug release for the microspheres. Kinetic modeling of in vitro dissolution profiles revealed the drug release mechanism ranging from diffusion controlled to anomalous type. Ethocel and HPMC K100M in a ratio of 1:3 exhibited better sustained release properties than 1:1 and 3:1 ratios. The release rate of gliclazide from microspheres prepared with Ethocel (20 cps) and HPMC K100M was less than the release rate of gliclazide from microspheres prepared with HPMC K100LV, demonstrating Ethocel and HPMC K100M as suitable polymeric blend for preparing the controlled release formulation for gliclazide whereas, HPMC K100LV was found not suitable candidate when used alone as a polymer. DOI: http://dx.doi.org/10.3329/dujps.v13i2.21893 Dhaka Univ. J. Pharm. Sci. 13(2): 149-166, 2014 (December)